The Routledge companion to African American art history
1 online resource.
Keywords: "This Companion authoritatively points to the main areas of enquiry within the subject of African American art history. The first section examines how African American art has been constructed over the 70 years of published scholarship. The second section studies how African American art is and has been taught in academia. The third section focuses on how African American art has been reflected in art galleries and museums. The final section opens up understandings of what we mean when we speak of African American art. This book will be of interest to graduate students, researchers and professors and may be used in African American art, visual culture, and culture classes"--